The Relationship Between Seasonal and Environmental Variations with Morphometric Characteristics of Sargassum polycystum (C. Agardh. 1824) from Tidung, Sebesi and Bintan Islands Waters, Indonesia - Sumandiarsa, I Ketut; Bengen, Dietriech Geoffrey; Santoso, Joko; Januar, Hedi Indra (Polish Journal of Natural Sciences, 2023)
Sargassum brown seaweed is one of the most morphologically complex genera due to environmental adaptation. Therefore, the relationship between seasons and different environments condition with the morphometric characters of Sargassum polycystum that grows in Tidung, Sebesi, and Bintan Islands waters is determined. Principal Component Analysis (PCA) is used to determine environmental variables’ contribution, and discriminant analysis was employed to differentiate variables between research locations. The results showed that there were variations in morphological characteristics between areas. Tidung Island showed an advantage in terms of the blades’ size, while Sebesi Island showed dominance in the diameter of the primary stipe, air bladder, and the branching distance from the holdfast. Additionally, we characterized the thallus’s length and the seaweed’s total length in the Bintan Islands. PCA shows that the main factors of water quality in ammonia, pH, Se, Fe, and Mn are associated with blade variations. On the other hand, there was a correlation between variations in DO and salinity with the branching distance from the holdfast and presence of nitrates, variations in temperature and brightness were correlated with holdfast diameter, thallus diameter, and blade size. This study found that the morphometric variation of S. polycystum was significantly influenced by the locations (small islands) and seasons.